The Effect of Baby Spa on the Sleep Duration of Babies Aged 3-12 Months at Independent Midwife Practice (TPMB) Mrs. S, Karawang Regency, Indonesia - Febriana, Rosita (Arkus, 2023)
Baby spa is a series of treatments designed specifically for babies, providing gentle massages, immersion in warm water, and other sensory stimulation. This method is believed to help babies relax more, relieve muscle tension, improve blood circulation, and reduce colic. Gentle massage and immersion in warm water can help babies feel relaxed. This study aimed to determine the effect of baby spas on the sleep duration of babies aged 3-12 months at independent midwife practice (TPMB) Mrs. S, Karawang Regency, Indonesia. This study is experimental research with a pre-post-test approach with the control group. This study uses primary data, namely measuring the length of sleep of babies aged 3-12 months. A total of 30 research subjects took part in this study. In the intervention group, it was found that most babies slept in the range of 14-16 hours, which is considered the standard duration. Meanwhile, most of the control group had less than 14 hours, which is classified as a short sleep duration. In conclusion, baby spa influences the sleep duration of babies aged 3-12 months at independent midwife practice Mrs. S, Karawang Regency, Indonesia.